PENGARUH KEPUASAN KERJA DAN IKLIM PSIKOLOGI TERHADAP ORGANIZATION CITIZENSHIP BEHAVIOR DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI - Rahayu Triastity, Ajeng Ferdika Sari, Alwi Suddin & (Universitas Slamet Riyadi, 2018)
This research aims to analyze the significance of the influence of jobsatisfaction and organizational commitment towards psychological climate.Analyze the significance of the influence of job satisfaction, organizationalcommitment and psychological climate against Organization CitizenshipBehavior. Analyse the influence of job satisfaction and psychological climateagainst Organization Citizenship Behavior that is mediated by thecommitment of the organization. The population in this study are allemployees of PT Tyfountex Indonesia staff of 91 people. The number ofsamples in this research as much as 91 employees, so it is a researchcensus. Methods of data collection were used: questionnaire. Technique ofdata analysis used the test of validity, reliability test, test the assumptions ofclassical, and path analysis. The results of the analysis of the data obtainedconclusions that: job satisfaction and psychological climate effect significantlyto organizational commitment. Job satisfaction, organizational commitmentand psychological climate effect significantly to Organization citizenshipbehavior of employees. Mediate the influence of organizational commitmentjob satisfaction and psychological climate against Organization citizenshipbehavior.Keywords: job satisfaction, organizational commitment, the psychologicalclimate, OCBÂ